Thixoforging of Low Carbon Steel SAE1006 Backward Thixoextrusion. (2017) - Becker, Eric; Bigot, Régis; Faverolle, Pierre
Abstract: For nearly two decades, researchers from academia and industry are working on the development of steel alloys thixoforging, which are not the easiest to form with this process. The early fundamental technology research demonstrated the feasibility for certain conditions. These works has focused on different steel grades, e.g. C38, M2…; different tools and their materials due to specific thermal and mechanical properties; better forming conditions; flow of the semisolid material; characteristics and the means of obtaining the semisolid state; evolution of the liquid fraction; mechanical models of deformation, process simulation, etc. Today, it is necessary to continue the development by realizing technological demonstrators integrating some industrial constraints, like production rate and costs, but it is also necessary to identify and define the field of application of this process and its limits in terms of materials, tools, cadence, forming speed, etc. The major difficulties are the interactions and the coupling of these various parameters and conditions of this forming process making it difficult to understand the mechanisms of thixoforging. In this context, a new steel grade was tested and studied. This SAE 1006 grade is deemed difficult to thixo-forge, due to its high melting point. The selected part geometries are not feasible with conventional forging. The present study reports the first results of the thixoforging of this steel for a product with specific geometric conditions and the means used and developed.